Ruling Russian Eurasia, Khans, Clans, and Tsars - Williams, Robert Chadwell 1938- (Anvil series, 2000)
An interpretative history of the Russian Empire from 1700 to 1917, in the larger Eurasian context of the Mongols, Muscany and the Soviet Union. It explains how a westernizing oligarchy tried to transform an enigma of clan societies into modern nation states, and it includes original documents.